Two in one: Neuregulin 1 improves cardiac diastolic and kindney funtcion in chronic kidney disease in rats. (25th November 2020) - Kiss, A; Acar, E; Watzinger, S; Kovacs, Z.S; Marvanykovi, F; Szucs, G; Csont, T; Siska, A; Foldesi, I; Podesser, B.K; Sarkozy, M
Abstract: Introduction: The prevalence of chronic renal disease (CKD) is continuously increasing in developed countries. Uremic cardiomyopathy characterized by left ventricular hypertrophy (LVH) and diastolic dysfunction (DD) is a common cardiovascular complication of CKD. Cardiac microvascular low-grade inflammation and altered expression of endothelium derived Neuregulin-1 (NRG-1) are contributed to left ventricular DD. Our aim was to charachterize the effects of CKD on the expression of NRG-1 and 2) NRG-1 treatment on myocardial hypertrophy, diastolic dysfunction and renal function in the rat model of CKD. Methods: Male Wistar rats were used and randomized into 3 groups: 1) Sham-operated, 2) CKD induced by 5/6 nephrectomy (CKD) and 3) NRG-1-treated CKD group (CKD+NRG-1). In this group, 2 weeks after the CKD induction, the rats were treated with recombinant human NRG-1 (rhNRG-1) at the dose of 10 μg/kg/d for consecutive 10 days with tail vein injection of NRG-1. Serum and urea creatinine levels were measured to verify the development of CKD and transthoracic echocardiography was performed to monitor cardiac morphology and function. Furthermore, total RNA was isolated and RT-qPCR was performed to evaluate the expression levels of inflammatory chemokine and cytokines (TNF-α, TGF-β). In addition, NRG-1 protein levels were assessed in both kidney and heart tissue by ELISA. To clarify the underling anti-fibrotic mechanism, human ventricular cardiac fibroblasts (HCF) were cultured and treated with the TGF-β (20 ng/ml), and TGF-β + hrNRG-1 for 24 h, respectively. Confocal microscopy was used to detect α-smooth muscle actin (α-SMA) expression, marker for fibroblast to myofibroblast transtion. Results: 10 weeks after the 5/6 nephrectomy, serum carbamide and creatinine levels were significantly increased and creatinine clearence was significantly decreased as compared to sham-operated animals proving the development of chronic kidney disease (CKD). This was accompanied by a significant decrease in NRG-1 protein expression levels in both cardiac and kidney tissue. Of note, NRG-1 treatment markedly reduced these changes, suggesting its renoprotective effects in CKD. In addition, In CKD animals, the significantly increased anterior, posterior and septal wall thicknesses with decreased end-diastolic and end-systolic diameters proved the development of concentric left ventricular hypertrophy. In CKD, the septal e' was significantly decreased and E/e' increased indicating the developemnt of diastolic dysfunction. These parameters were significantly improved by NRG-1 treatment. Mechanistically, NRG-1 treatment reduced the expression of inflammatory cytokines in compared to untreat group. Furthermore, TGF-β induced α-SMA and Col I upregulation was markedly reduced by hrNRG-1 treatment. Conclusions: NRG-1 treatment improved both renal and cardiac funtion in CKD, via a mechansim including the anti-inflammatory and anti-fibrotic properties of NRG-1. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Österreichischer Austauschdienst